Walter White's Moral Transformation in the Breaking Bad Series: A Semiotic Analysis Based on Friedrich Nietzsche's Six Tasks of the Camel Spirit - Dimas Anargya Bhagaskara; Maylanny Christin (Eduvest - Journal of Universal Studies, 2025)
This study examines the moral transformation of Walter White in the Breaking Bad series through a semiotic analysis based on Friedrich Nietzsche's concept of the "Six Tasks of the Camel Spirit" as outlined in Thus Spoke Zarathustra. The research aims to explore how Walter White's character evolves from a mild-mannered teacher into a ruthless figure, driven by a personal quest for power and control, by analyzing the visual and narrative signs that represent his psychological, moral, and ideological changes. Using Roland Barthes’ semiotic framework, the study decodes the denotative, connotative, and mythic meanings in key scenes that mark crucial moments of transformation in Walter’s character. Nietzsche’s philosophy, particularly the tasks related to self-overcoming and the rejection of herd morality, provides a philosophical lens through which Walter’s moral journey is understood. The findings highlight how Breaking Bad represents a complex interplay between visual symbolism, narrative structure, and moral philosophy, shedding light on the ways in which media shapes and reflects individual and collective values. This study contributes to the field of media and cultural studies by offering a critical model for understanding moral transformations in contemporary television narratives..